Social Worlds and Festive Spaces in the Yawar fiesta of José María Arguedas - Castillo Guzmán, Gerardo (2018)
The following paper explores the social world that José María Arguedas constructs in his novel Yawar Fiesta. The depicted social world is a fragmented one where diverse social archetypes interact each other in a highly hierarchical universe where they share common cultural codes that oppose the Andean world of Puquio against modernizing elements of the coast. The paper concludes that the resolution of that cultural opposition is reached through the carnival reversal of the es- tablished social order.